The Ethical Marketing Leadership in PRC Consumers’ Purchase Judgment toward Thailand’s Organic Rice Consumption - Baoguo, Li; Laksitamas, Prin (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The research on the formation mechanism of ethical purchase behavior of organic agricultural products is a relatively new research trend, which will have great research potential in the future. This study aimed to analysis the key factors (ecological ethics, social ethics, and cultural ethics and international marketing ethics) are affected on Chinese consumers’ ethical purchase decision-making toward Thailand’s organic rice consumption. The quantitative research which employed 35 instruments were questionnaires. The research samples consisted of 620 Chinese consumers from four major Chinese cities (Beijing, Shanghai, Guangzhou, Chengdu), obtained by random sampling technique. Data analysis was using exploratory factor analysis, confirmatory factor analysis and structural equation modeling (SEM). The results showed that the key factors (ecological ethics, social ethics, and cultural ethics and international marketing ethics) were positive affected on Chinese consumers’ ethical judgment, and Chinese consumers’ ethical judgment were positive affected on purchase decision-making toward Thailand’s organic rice consumption. The key factors (ecological ethics, social ethics, and cultural ethics and international marketing ethics) were positive affected on purchase decision-making through Chinese consumers’ ethical judgment as mediator. The strategic suggestions for Chinese consumers to build values and attitudes towards ethical consumption, cultivate ethical consumption lifestyles and improve consumers’ ethical purchasing ability. For enterprises to set the reasonably price and improve the distribution channels of organic agricultural products of consumers’ ethical perception, enhance the ethical scene marketing of organic agricultural products. For government and relevant organizations to improve trust mechanism and provide technical and policy support to the organic agricultural products consumption.